Digitalization of Islamic Religious Education Learning and Children's Moral Values Management and Competency Analysis of teachers at PAUD Satya Prawira Academic Year 2024-2025 - Ramzi, Muhajirin; Eliyana, Eliyana (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
In the 21st century, digital literacy is like a foundation to support a person's life, especially for young children, so that digital literacy is used as a teaching material, one of which is done by communicating via internet networks or utilizing social media by using digital media such as laptops or cellphones. which of course is not far from adult supervision. The development of the times is increasingly advanced, various discoveries and technological advances are increasingly real and have an impact on every aspect of life where not only adults feel it, but children are also involved in experiencing these technological advances so that digital literacy is now widely applied in good life. in the school environment and outside the school. This research aims to analyze the management and competence of teachers in learning in instilling Islamic religious and moral values and the implementation of digital-based learning media at PAUD Satya Prawira. Based on the results of this research, it provides recommendations that digital-based Islamic learning media in Satya Prawira PAUD can be used more optimally in the learning process and teachers are able to provide good learning in accordance with competency.